Impact of corporate donations to combat Covid-19 on the market value of donor companies: an analysis from the perspective of legitimacy theory - Krauspenhar, João Henrique; Pescador, Rafael Bertoldi; Rover, Suliani; Ferreira, Denize Demarche Minatti; Van Bellen, Hans Michael (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The objective of the study is to verify the impact of corporate donations aimed at combating Covid-19 on the market value of the involved companies. Methodology: We employ the event study methodology, examining the returns of company shares on the dates when corporate donations were announced. Results: Results indicate an increase in the standard deviation of daily returns of Itaú, Vale and JBS shares compared to Ibovespa. For Itaú, three statistically significant abnormal returns occurred during the event window, with two being negative and only one positive, thus the negatives prevailed. In the case of Vale, there was one significant abnormal return of each kind prior to the event, and one positive return on the event day. For JBS, five statistically significant abnormal returns were observed during the event window, with three being positive and two negatives. Therefore, the hypothesis that corporate donations during the Covid-19 pandemic positively impact the market value of donors was partially confirmed for Vale and JBS, but not for Itaú. Contributions of the Study: The study concludes that acts of corporate social responsibility (CSR) positively impact the market value of the practicing companies. Additionally, it suggests that the impact on market value varies among companies based on the nature of the threat to their legitimacy, with those facing threats originated from individual responsibility showing a positive impact.